Relationship between information sharing and flexibility in management of enterprises in automotive industry: an empirical study - Veselovská, Lenka; Kožárová, Mária; Závadský, Ján (Serbian Journal of Management, 2018)
This paper focuses on the topic of relationship between flexibility of supply chain and information sharing among partners with emphasis on their managerial practices. Since nowadays competition increases, enterprises give more importance to their supply chain management. Our paper provides a complex look on the issues of flexibility and information sharing in Slovak automotive industry and their interdependences. The main aim of this study is to identify relationships between shared information and flexible parameters of supply chains in automotive industry. Achieved results provide a current image of how supply chain management is handled in Slovakia’s most significant industry. Our findings indicate that there is a significant dependence between types of information shared and different flexibility types.